A Proposed Information System for Communicating Foot-and-Mouth Disease Events among Livestock Stakeholders in Gairo District, Morogoro Region, Tanzania. (21st April 2021) - Kijazi, Ahmed; Kisangiri, Michael; Kaijage, Shubi; Shirima, Gabriel
Abstract : Foot-and-Mouth Disease (FMD) is present in many countries globally, including Tanzania, especially Gairo district. The data shows that 78% of livestock keepers in Gairo district had already observed FMD infection in their cattle, and the pastoral communities were mostly affected. Currently, vaccination is the main tool for controlling FMD because there are no therapeutic intervention tools. Therefore, effective communication among livestock stakeholders can be used as an essential tool of preparedness for the disease's impact. This study had two specific objectives: (i) to explore the challenges of communicating FMD events among livestock keepers and other livestock stakeholders in Gairo district and (ii) to propose an information system for sharing FMD events among the livestock stakeholders in Gairo district. The study found that there was a delay when communicating FMD events in Gairo district due to the long chain of information flow. Therefore, the system aims to reduce the communication chain by allowing livestock keepers to report disease outbreaks directly to the system. Livestock keepers may also access FMD precaution measures, negative impacts, clinical signs transmission ways, and current outbreaks directly from the system using Unstructured Supplementary Service Data (USSD), Short Message Services (SMS), robocalls, and feature phones. The system also provides a common platform for sharing FMD outbreaks data and events to other stakeholders based on the system's privileges. In this study, a closed-ended interview using a questionnaire was used for data collection. The PHP hypertext processor, jQuery, HTML, JSON, JavaScript, Apache web server, and MySQL database were used for developing the system.